Portrait of the Artist as a White Pig : Poems - Gentry, Jane (Book collections on Project MUSE., 2006)
These rich, lyrical poems, written by Jane Gentry over ten years, register the resonance between the poet's inner being and the outer world's everyday events. Moments of insight -- gained while watching a roofer at work next door, napping with the cat, reading on the porch, carrying the laundry, or strolling the aisles of Sam's Club -- expose the bright bones of the swiftness of time's passage, reminding us to stay attentive. Gentry's poems are deeply grounded in the continuity of family and homeplace yet also embrace new experiences. The juxtaposition of the ordinary and the beautiful, the paradox of the mundane and the artistic -- whether in nature, in relationships, in memories, or in the body -- are the hallmarks of her second collection. The years took our house, cool and dark, generous as a healthy heart, where in September a cricket sang under the kitchen hearth. They took my mother with her red hair and her creamy skin, and my father whose laughing head shone with the fire of summer as he shoveled corn to his pigs. When I awoke one day, my bloom was past. Those who loved me first were dead, and promises had blown away like chaff or clouds, which dazzle now only in the moment of their height and roll. The years have given back the thing itself. -- from "My Life Story."